Pedagogical-Psychological Possibilities Of Professional-Methodological Training Of The Future Teacher Of Fine Arts - Bekmuratova Shakhida Ne’matjonovna (Global Scientific Publishing, 2023)
This article covers the current issue, the pedagogical and psychological possibilities of professional and methodical training of the future art teacher.
Keywords: perspective; color science; optics and light and shadow laws